Integration of Customary Criminal Law into the National Legal System: Opportunities and Challenges - Afnaini, Afnaini; Hamdan, Hamdan (SEAN Institute, 2025)
The purpose of this study is to examine the advantages and disadvantages of incorporating customary criminal law within the national legal framework of Indonesia. The local justice principles of customary criminal law, which is rooted in indigenous communities, frequently diverge from those of the national criminal justice system, which is focused on legal positivism. The incorporation of customary criminal law has emerged as a key concern in legal reform with decentralization and the constitutional recognition of indigenous communities. The research method used is juridical-normative with analysis of laws and regulations and court decisions. According to the study's findings, Indonesia's law enforcement system might benefit greatly from customary criminal law, particularly in achieving restorative and contextual justice that aligns with the local values of indigenous people. The significance of living law in society as a supplement to national law is highlighted by the recognition of customary criminal law by Law Number 1 of 2023 respecting the Criminal Code. Although there are still issues with legal harmonization, the legality principle, and the limitations of customary institutions, this study also discovered that regional regulations governing customary criminal law can improve the legitimacy and efficacy of customary law enforcement.